2023
DOI: 10.1111/1475-6765.12624
|View full text |Cite
|
Sign up to set email alerts
|

Still proud at the polls? LGBT+ rights don't dilute the sexuality turnout gap

MICHAL GRAHN

Abstract: Recent research has shown that sexual and/or gender minority voters are prone to mobilizing when LGBT+ issues are on the political agenda. This increased level of political engagement is attributed to the experience of discrimination, understood both in legal and social terms, which spurs LGBT+ individuals to participate with the aim of advancing their rights. However, a crucial question remains unanswered: do these gaps in participation persist in contexts where core LGBT+ rights are protected? Drawing from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Following this perspective, an increasing number of empirical studies have been devoted to the political behaviour, i.e. voting participation and voting behaviour, of LGB individuals and have demonstrated that this social group, which is still only marginally researched, might be and is capable of shaping politics (Guntermann and Beauvais, 2022;Grahn, 2023;Hertzog, 1996;Perrella et al, 2012;Turnbull-Dugarte, 2020b;Wurthmann, 2023a). In contrast, the literature on LGB politicians and their political behaviour was considered "almost nonexistent" (Everitt, 2015, 178) only a few years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Following this perspective, an increasing number of empirical studies have been devoted to the political behaviour, i.e. voting participation and voting behaviour, of LGB individuals and have demonstrated that this social group, which is still only marginally researched, might be and is capable of shaping politics (Guntermann and Beauvais, 2022;Grahn, 2023;Hertzog, 1996;Perrella et al, 2012;Turnbull-Dugarte, 2020b;Wurthmann, 2023a). In contrast, the literature on LGB politicians and their political behaviour was considered "almost nonexistent" (Everitt, 2015, 178) only a few years ago.…”
Section: Introductionmentioning
confidence: 99%